In vivo osteogenesis of plasma sprayed ternary-ion doped hydroxyapatite coatings on Ti6Al4V for orthopaedic applications. Issue 8 (15th April 2022) - Ratha, Itishree; Datta, Pradyot; Chand Reger, Nimu; Das, Himanka; Balla, Vamsi Krishna; Devi, K. Bavya; Roy, Mangal; Nandi, Samit Kumar; Kundu, Biswanath
Abstract: Plasma-sprayed hydroxyapatite (HAp) coated metallic implants for orthopaedic and dental application have some inherent shortcomings like brittleness, low fracture toughness, poor tensile strength, slow osseointegration rate and poor antimicrobial properties. To mitigate these shortcomings, we have envisaged and developed specific compositions of Sr, Zn, Ag and F multi-ion doped HAp earlier employing Taguchi statistical principle. The aim of the present investigation is to study the feasibility of plasma spray-coated metallic implants focusing specifically on two specific compositions {based on Sr–Zn–F-HAp – (D1HAp-Ti) and Sr–Zn–Ag-HAp (D2HAp-Ti)} as envisaged earlier. Performance of the above compositions was studied and compared with no coating and pure HAp coated implants. The comprehensive study included detailed material development and characterization up to in vivo pre-clinical trial. Finally, free-flowing granules (75–104 μm) of multi-ion doped HAp were used for plasma spray coating on Ti6Al4V substrate and analyzed the effect of multi-ion doping on HAp. Interestingly, XRD showed presence of HAp as main phase in all cases except undoped HAp coating where secondary phases like α-TCP and β-TCP could also be traced. FTIR study confirmed basic functional groups of HAp for all cases. Scratch adhesion of coating as well as microhardness was found to be increased substantially by multi-ion doping The result from corrosion resistance and SBF immersion test clearly exhibited multi-ion doped HAp coated implant's superior property co over undoped HAp coating. In vivo implantation of these implants in animal femur defect model and follow up investigation up to 2 months with micro-CT, histology, radiology and fluorochrome labelling showed enhanced osseointegration of multi-ion doped samples as compared to bare, and control samples. . Hence, a multi-ion doped HAp coated titanium substrate can be used as a promising implant coating material for orthopaedic applications.